A Syllabus Design in Learning Speaking for International Volunteers as Non-Native Speakers of Indonesian - Laily Nur Affini (ETERNAL (English Teaching Journal), 2019)
Indonesia International Work Camp (IIWC) is an international organization. The organization facilitates Indonesian course to foreign volunteers who conduct a voluntary project in Indonesia. The course started in 2009 up to now. If there is one lack from the course, it is because the course did not have any syllabus. This action research study has a main purpose to design an Indonesian speaking syllabus for IIWC foreign volunteers based on contextual field at a project site. This action research included a basic action research routine: look, think and act. An approach employed in this research is case study. Questionnaires, interviews, notes, a teaching journal, recordings, photographs and videos were taken during the course process. The population of this research is the IIWC foreign volunteers. The sample of this research is Yurie Takahashi, a Japanese foreign volunteer who was the only new foreign volunteer came in Indonesia at that time. She conducted a social international voluntary service in Indonesia. The major research participants are I as the Indonesian speaking instructor, and the foreign volunteer as the learner. The collected data is analyzed using a process of reflection and interpretation that is categorizing and coding. The findings are:  the syllabus for Indonesian speaking course, for IIWC foreign volunteers who conducted a project at the project site of Fatimatuzzahro orphanage Semarang central-Java Indonesia. The syllabus employs a learning centered approach. Then the program evaluation revealed the instructor’s teaching and attitudes from the learner’s perspective and the learner’s progresses after joining the course. Eventually, the teaching materials compilation was taught from the syllabus made to be a handout of the course which can support the teaching-learning processes later. It is suggested to other IIWC’s Indonesian speaking instructors who will teach foreign volunteers at the orphanage can look at the syllabus in advance, so that they can know starting points in surveying the existing situation. It is also suggested to other researchers to take the uninvestigated cases in this research regarding Indonesian listening and pronunciation problems which later can be contributed as well to knowledge of applied linguistics.